Three-dimensional tilted hydromagnetic natural double-diffusive convection in a rectangular cuboid filled with nanofluids based on magnetic nanoparticles - Al-Balushi, Latifa M.; Uddin, Md. J.; Rahman, Mohammad M.; Öztop, Hakan Fehmi; Pop, Ioan (Wiley, 2022)
In this article, we use magnetic nanoparticles to explore the three-dimensional natural upward force flow within a quadrangular cuboid under the influence of a sloping magnetic flux. We consider three forms of thermic conditions on the bottom surface of the cavity, such as uniform surface temperature, constant heat flux, and temperature varied parabolically in space. The Galerkin-type finite element method is used to solve the unitless leading equations of implicit physical systems. Ferrite-water nanofluid is the default, used to study the flow field, thermal field, and concentration field other than the regular Nusselt number. We examined the influence of many model parameters, especially the thermal Rayleigh number, volumetric nanoparticles fraction, the Hartmann number, nanoparticles formation, and the predisposition of magnetic flux. The influence of the position of the thermal flux on the lower surface of the thermal field cavity is also studied. The heat transfer rate of various magnetic nanofluids is compared. Our simulated data echoed nicely with the available experimental one. The results show that Mn-Zn ferrite-kerosene nanofluid exhibits advanced heat transportation more than the other nanofluids studied. For lower dimensions of aspect ratio and nanoparticle diameter, higher heat transfer is obtained. Compared with other boundary conditions studied, the uniform temperature on the bottom surface of the cuboid provides a higher heat transfer rate.
Keywords: finite element method; free convection; magnetic nanoparticles rectangular cuboid; nanofluid; sloping magnetic field